Insurance against local productivity shocks - Fernando Pérez-Cervantes (Banco de México, 2016)
I slightly modify the model of Monte et al. (2015) to estimate how workers in Mexican municipalities choose the location of their workplace based on the income gains from commuting to another municipality. Estimates are in line with the intuition: Static estimates for both 2010 and 2015 suggest that those who commute earn an average 30 percent more than their non-commuting counterparts, and that commutes tend to be to municipalities located close to the place of residence. Comparing both years suggests that a reduction in local productivity both decreases the number of workers that come from other municipalities and increases the number of local residents that decide to work somewhere else, mitigating the negative effect of the reduction in local wages with higher earnings from the new work destinations. I find that some municipalities were not able to mitigate the negative productivity shocks on their income.
Keywords: F1; R1; J6; O2; 330; Commuting; Economic Geography; Mexico